2022
DOI: 10.1007/s11748-022-01772-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil to lymphocyte ratio on acute kidney injury after on-pump coronary artery bypass: a retrospective, single-center study

Abstract: Objective To investigate the predictive value of preoperative neutrophil to lymphocyte ratio (NLR) on acute kidney injury (AKI) after on-pump coronary artery bypass (ONCAB). Methods Patients who underwent elective ONCAB for coronary heart disease were included. NLR was calculated according to the results of preoperative routine blood test, patients were divided into non-AKI and AKI groups, and the differences in clinical baseline data between the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…From 10 studies 41–50 involving 7660 patients, we found a statistically significant association between elevated preoperative NLR and postoperative AKI (OR 1.45, 95% CI 1.18–1.77) (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…From 10 studies 41–50 involving 7660 patients, we found a statistically significant association between elevated preoperative NLR and postoperative AKI (OR 1.45, 95% CI 1.18–1.77) (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
“…Twelve studies 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 involving 10,724 participants undergoing cardiac surgery were included. Detailed characteristics of included studies can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil lymphocyte ratio (NLR) is one of the most commonly used parameters. In a recent study, it was shown that a preoperative high NLR value could predict the risk of AKI after CABG operations accompanied by CPB 3 . Syndecan-1 (SDC-1) is an important indicator of endothelial glycocalyx damage, which plays an important role in the pathophysiology of AKI 4 .…”
Section: Introductionmentioning
confidence: 99%